Characterization of the complete chloroplast genome of Chrysanthemum oreastrum (Asteraceae) as a traditional medicinal plant to China. Issue 2 (2nd April 2020) - Feng, Hui; Xu, Hong; Chen, Jianyong; Zheng, Hongxia; Ye, Yiming; Liu, Yi
Abstract: Chrysanthemum oreastrum is a perennial herb of Compositae and one of the traditional Chinese medicinal herb in China. In this study, the complete chloroplast genome of C. oreastrum was illustrated to add more genetic information. The chloroplast genome is 151, 045 bp in length as the circular, which consists a large single-copy region (LSC) of 82, 793 bp, a small single-copy region (SSC) of 18, 348 bp and a pair of inverted-repeat regions (IRs) of 24, 952 bp. The overall nucleotide composition of chloroplast genome is: 47, 014 bp A (31.1%), 47, 399 bp T (31.4%), 27, 963 bp C (18.5%), 28, 699 bp G (19.0%), and the total G + C content of 37.5%. 128 species genes were annotated that included 85 protein-coding genes (PCGs), 35 transfer RNA (tRNAs), and 8 ribosome RNA (rRNAs). Phylogenetic relationship indicated that C. oreastrum is closely related to C. morifolium in the genetic relationship constructed using the maximum-likelihood (ML) method.